Análisis del periodismo deportivo en medios de comunicación en época de pandemia - Suárez Cando, Ángel (2021)
This case study was carried out with the topic of the analysis of sports journalism in the media in times of pandemic, with the aim of analyzing sports journalism in the pandemic, in addition to identifying the risks of the media during mandatory confinement by Covid-19. Journalism is a universal communication method, with the temperament of informing and expressing opinions, which responds to social functions, according to the deficiencies of individuals to inform, know where it happens and propose ideas about what society thinks. The main objective of journalism is implemented throughout life when information is disseminated, the purpose is to protect the community in daily activities, so that information can be imparted in important rights, and information in the community should not be omitted for its implementation. The COVID-19 disease that caused the pandemic is unique: Accurate investigations are a waste, but this work faces current and expected transients. In recent months, the country has been a place of frequent and severe degradation, including a systematic end: publications stopped being shared. The current crisis caused by Covid-19 has brought terrible working conditions and methods of interaction in the media, they had to design remote office work methods to continue the corresponding work.